2012
DOI: 10.1002/adma.201203664
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Room‐Temperature Conversion of Copper(II) Hydroxide into HKUST‐1 (Cu3(btc)2)

Abstract: Copper(II) hydroxide is converted directly to HKUST-1 (Cu(3) (btc)(2) ) after only 5 min at room-temperature in aqueous ethanolic solution without the need of additional solvents. Scale up to the kilogram scale does not influence porous properties yielding pure-phase product with a remarkable total surface area exceeding 1700 m(2) g(-1) featuring aggregates of nanometer-sized crystals (<600 nm) and extremely high space-time yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
165
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(176 citation statements)
references
References 23 publications
8
165
1
2
Order By: Relevance
“…The nanofibrous MHN porous networks not only serve as the metal source but also firmly confine the functional species during MOF growth. Our recent work confirmed that MHN thin films can be rapidly converted to MOF thin films through an outside-inner growth process involving immersion in an organic ligand solution at room temperature 10 , similar to the conversion of copper hydroxide NPs to HKUST-1 crystals at room temperature 48 . The initial outer MOF layer prohibits escape of the pre-embedded functional component significantly, there is no limitation of the size, dimensions and shape, or classification of the encapsulated functional components, which can be ions, nanoparticles, polystyrene (PS) spheres with sizes ranging from less than 1 nm to several micrometres, one-dimensional single-walled carbon nanotubes (SWCNTs), bioactive proteins or micrometre-sized PS spheres.…”
supporting
confidence: 69%
“…The nanofibrous MHN porous networks not only serve as the metal source but also firmly confine the functional species during MOF growth. Our recent work confirmed that MHN thin films can be rapidly converted to MOF thin films through an outside-inner growth process involving immersion in an organic ligand solution at room temperature 10 , similar to the conversion of copper hydroxide NPs to HKUST-1 crystals at room temperature 48 . The initial outer MOF layer prohibits escape of the pre-embedded functional component significantly, there is no limitation of the size, dimensions and shape, or classification of the encapsulated functional components, which can be ions, nanoparticles, polystyrene (PS) spheres with sizes ranging from less than 1 nm to several micrometres, one-dimensional single-walled carbon nanotubes (SWCNTs), bioactive proteins or micrometre-sized PS spheres.…”
supporting
confidence: 69%
“…This conclusion is supported by previous studies into converting other Cu-based ceramics into HKUST-1. 45,46,57 In order to gain further insights into the growth of the HKUST-1 crystals, in situ small-angle X-ray scattering (SAXS) and wide-angle X-ray scattering (WAXS) measurements were conducted at the Australian Synchrotron. For these measurements, the Cu-based precursor materials were placed in a capillary with the mixed solution of EtOH and water, followed by the controlled addition of the alcoholic solution containing the H 3 BTC linker using a syringe.…”
Section: Resultsmentioning
confidence: 99%
“…water/ alcohol at room temperature) with short processing times. 45 Here we describe a simple approach to incorporate magnetic nanoparticles into MOFs by taking advantage of the method developed in our previous study, as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…[8] For example, Majano et al [9] were the first to synthesize HKUST-1 [Cu 3 (BTC) 2 ] (BTC = benzene-1,3,5-tricarboxylate) with copper hydroxide as the precursor. The conversion of Cu(OH) 2 into HKUST-1 could be carried out at room temperature and is suitable for large-scale production.…”
Section: Introductionmentioning
confidence: 99%